2009
DOI: 10.4054/demres.2009.21.26
|View full text |Cite
|
Sign up to set email alerts
|

Couples’ decisions on having a first child

Abstract: We investigate the decision-making process of having a first child, using theories on individualisation, lifestyle choices and negotiating partnerships as a starting point. We compare couples who had their first child at a relatively young age with those who had their first child at an older than average age, using data from semi-structured interviews with 33 couples, selected from the Netherlands Kinship Panel Study (NKPS). Although expecting more explicit decision-making among older parents, our qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 37 publications
(38 reference statements)
1
26
0
2
Order By: Relevance
“…This conservative approach toward childbearing is consistent with theories of rational choice, risk aversion and gender equity [37]. In study by Rijkin (2009), concerns about age and losing childbearing opportunities due to reproductive biological clock were proposed by majority of women [38].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This conservative approach toward childbearing is consistent with theories of rational choice, risk aversion and gender equity [37]. In study by Rijkin (2009), concerns about age and losing childbearing opportunities due to reproductive biological clock were proposed by majority of women [38].…”
Section: Discussionmentioning
confidence: 77%
“…The study of Rijken (2009) in the Netherlands showed that limited freedom was a very important issue in childbearing decision making. In the Netherlands Fertility and Family Survey, 50% of men and women who had not any child up to 30 years old (women) or 33 years old (men) mentioned that the desire to enjoy their freedom was the main reason for delaying childbearing [38].…”
Section: Discussionmentioning
confidence: 99%
“…Some couples consider having children early in their marriage a threat to the chance of being alone with their spouse and enjoying their freedom, pursuing fun activities, traveling and spending time together, and thus delay their childbearing decision-making. Moreover, the uncertainty about fully knowing one's spouse (especially in the case of traditional marriages) and feelings of doubt about the stability of the marital relationship caused by disputes and consuming discussions over the course of getting to know one another lead to childbearing hesitations (Kariman et al, 2014b;Kariman et al, 2014a;Testa et al, 2012;Kariman et al, 2015;Klobas, 2011;Rijken, 2009;Samadaee-Gelehkolaee et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A long-term process of reflection and intellectual debate may therefore precede childbearing. Previous studies on fertility have failed to take into account the process of childbearing decision-making (Rijken & Knijn, 2009;Kariman et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have overcome this limitation have indicated that both members of couples who experience first childbirth at later age usually value personal fulfillment but struggle more with childrearing responsibilities and constraints than their younger counterparts (Rijken & Knij, 2009;Schlesinger & Schlesinger, 1989). However, Van Balen (2005 showed that the age differences related to personal fulfillment, partnership, identity and social status have no expression among men.…”
mentioning
confidence: 97%